Driving the polymerization of PEDOT:PSS by means of a nanoporous template: Effects on the structure. (17th December 2019) - Pinna, Andrea; Casula, Maria Francesca; Pilia, Luca; Cappai, Antonio; Melis, Claudio; Ricci, Pier Carlo; Carbonaro, Carlo Maria
Abstract: Poly(3, 4-ethylenedioxythiophene) (PEDOT) polymerization has been carried out both in a template-free environment and inside the nanopores of SBA-15 mesoporous silica. Comparing the two methods and the secondary doping of commercial PEDOT:PSS, we were able to study the structural effect of the templated polymerization via a multi-technique approach. We found that the confined polymerization favours a more linear configuration of the polymer chains, in a similar way to the well-known secondary doping with organic solvents. Moreover, comparison of computational and experimental results suggests that the PEDOT mean chain length is greater when the polymerization occurs in the nanoporous template, promoting the formation of a polymer with larger molecular weight and crystallinity. Graphical abstract: Image 1 Highlights: A multi-technique experimental approach has been used to deeper investigate PEDOT structural transition effects. MD and DFT calculations were performed to study PEDOT vibrational levels and XRD patterns as a function of chain length. Polymerization with SBA-15 mesoporous silica as template has been performed. Experimental and computational study suggest the formation of more linear, crystalline and longer polymer chains.